A new multi-level inverter with reverse connected dual dc to dc converter at simulation. (2nd January 2022) - Can, Erol
ABSTRACT: It is very important to drive loads and control the electrical devices with changing electrical energy levels and change a voltage form. While DC-DC converters are used to change the value level of direct current (DC) electrical energy, inverters are used to change its form such as alternating voltage. Unlike these studies in the literature, for the first time, dc-dc converters are used to a new device structure to convert dc electrical energy into alternating current (AC) electrical energy and they can also change an amplitude of the multi-level voltage. So, the paper presents a multi-level inverter with reverse connected dual dc to dc converter. Firstly, the circuit structure and the signals that control the circuit are given and the operating logic is explained. Then, the proposed circuit is gradually modeling in MATLAB Simulink. After that, the circuit is operated in MATLAB Simulink and its performance is measured. According to the results obtained, the new circuit structure gives hıghly successful results.